2012
DOI: 10.2310/jim.0b013e3182408549
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Blood Periostin Decrease after Acute Myocardial Infarction and are Negatively Associated with Ventricular Function after 3 Months

Abstract: Acute myocardial infarction is associated with a decrease in blood PN levels, and PN concentrations predict cardiac function 3 months after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
2
17
1
3
Order By: Relevance
“…In addition, the genotype of periostin was significantly correlated with plasma periostin level ( r 2 = −0.490, P < .039) and concluded that plasma periostin could be a promising biomarker for the estimation of early risk of CAD . However, in other study periostin levels were observed significantly lower in patients with acute myocardial infarction (AMI), after 1.3 ± 1.2 days as compared to the CAD and control group, respectively (175 ± 60, 245 ± 68, and 232 ± 63 ng/mL, P < .001) …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, the genotype of periostin was significantly correlated with plasma periostin level ( r 2 = −0.490, P < .039) and concluded that plasma periostin could be a promising biomarker for the estimation of early risk of CAD . However, in other study periostin levels were observed significantly lower in patients with acute myocardial infarction (AMI), after 1.3 ± 1.2 days as compared to the CAD and control group, respectively (175 ± 60, 245 ± 68, and 232 ± 63 ng/mL, P < .001) …”
Section: Resultsmentioning
confidence: 94%
“…33 However, in other study periostin levels were observed significantly lower in patients with acute myocardial infarction (AMI), after 1.3 ± 1.2 days as compared to the CAD and control group, respectively (175 ± 60, 245 ± 68, and 232 ± 63 ng/mL, P < .001). 34 Positive correlation was observed between Killip class (r = 0.395, .001). Similarly, the serum periostin level was found significantly higher in KD patients (42 549 ng/mL), when compared with febrile controls (P < .0086).…”
Section: Clinical Studiesmentioning
confidence: 92%
“…16 Proteolysis induces secretion of extracellular domains, which together with a large group of noncanonical ligands may modulate Notch signaling. 24 Periostin (POSTN), a matricellular protein functioning as a noncanonical Notch ligand, 25 is regulated in clinical myocardial injury, 26 and is associated with cardiac dysfunction in end-stage HF. 22,23 To our knowledge, DLL1 is the only detectable canonical Notch ligand in human plasma/serum.…”
Section: Introductionmentioning
confidence: 99%
“…For noncanonical Notch ligands, delta-like 1 homologue (DLK1) is the most studied and has inhibitory effects on angiogenesis. 24 Periostin (POSTN), a matricellular protein functioning as a noncanonical Notch ligand, 25 is regulated in clinical myocardial injury, 26 and is associated with cardiac dysfunction in end-stage HF. 23 POSTN may modify Notch signaling through inhibition of DLK1 27 or maintenance of Notch1 receptor expression.…”
Section: Introductionmentioning
confidence: 99%
“…Gene polymorphisms analysis in Chinese population showed that rs3829365 of the periostin gene was associated with susceptibility to, and severity of heart failure, suggesting a role of periostin in disease prediction and severity assessment [23]. Acute myocardial infarction patients showed decreased circulating level of periostin compared with control volunteers and periostin level was in negative correlation with patients’ cardiac function three months after AMI [24]. All these studies demonstrated that periostin acted as an important factor in the process of extracellular matrix remodeling under cardiac adverse conditions such as damage and pressure overload.…”
Section: Discussionmentioning
confidence: 99%